Solución informática para mejorar la eficacia en el proceso de registro de evaluación y asistencia del instituto de educación superior tecnológico público Chocope, a partir del año 2015 - Córdova Otero, Juan Luis (2016)
The following research, part of the current context of technological higher education in Peru, ie taking into account the policies and standards set by the state in non-university higher education. In this context the process of educational evaluation is given, respecting the various concepts and definitions of the same generic. Taking as its starting point the educational evaluation, we have the assessment of technological higher education, since in this range are considered other guidelines and policies to carry out this process. Thus we have the evaluation begins with definitions of competencies and skills to evaluate, using appropriate criteria and indicators. These results are recorded through physical media (documents) proposed by the ministry of education. This is the current processing of the registration process evaluation and attendance of students in higher technological education. Because of the way to carry this process, which affects both students, teachers and administrators, we have: dissatisfaction about not getting timely information and classified; record high number of complaints in the management of the evaluation and attendance of students; registration prolonged to a question about incidents of a student or group of students and inappropriate costs in the registration process evaluation and assistance. Faced with this problem, various registration processes evaluation and assistance in designing and implementing an IT solution is automated; and the right direction of ICTs that owns the school, was improved to some extent, the effectiveness to be classified and timely information for better decision-making, thereby overcoming largely negative consequences mentioned above, by setting aside the manual way of doing things, as was at first. For the modeling, analysis, design, implementation and deployment of the software solution, the RUP methodology was used (Rational Unified Process). For programming languages such as JavaScript and PHP. As manager MySql database and as Apache server. The most striking finding is that automating various both administrative processes as academics and complemented with proper direction of ICT in the educational institutions of non-university higher education, optimization and efficiency is achieved, thus achieving mitigate various problems to be presenting. Finally, a recommendation, we must highlight the importance of investigating or looking to automate those processes academic future lead to problems like the focus in this thesis; and establish best practices in the management of ICT as the ideal complement to achieve the effectiveness of the various academic activities in higher education institutions.